Factores de riesgo y protectores que influyen en adolescentes para el consumo de sustancias psicoactivas en la urbanización Finzenú de la ciudad de Montería, 2022-01 (2022)
The consumption of psychoactive substances is currently considered a social phenomenon that especially affects adolescents, the prevalence of use and abuse of substances in the adolescent stage are high, given the high availability, currently adolescents have to learn to live with drugs, making decisions about their consumption or abstinence from them. Objective: To determine the risk and protective factors in adolescents for the consumption of psychoactive substances in the Finzenú urbanization of the city of Montería, 2022-01. Methodology: Descriptive, cross-sectional study. The population was made up of 50 adolescents from the Finzenú urbanization in the city of Montería. The participants were selected using the non-probabilistic sampling technique, stratified by coexistence. Results: The main sociodemographic characteristics of the research show that the highest percentage of participants are women with 60%, the group with the highest age range is found in 14 to 6 years with 64%; Single marital status predominates, socioeconomic stratum 1, they come from the urban area, 22% do not study, 10% work, 48% displaced, 74% live with parents and 26% with grandparents. In the risk factors identified with the highest prevalence for adolescents in the Finzenú urbanization in the city of Montería, they are emotional discomfort with 60%, assessment of SPA with 68% and social permissiveness and accessibility to SPA with 52%. In the protective factors present in the adolescents of this research, interpersonal relationships prevail with 72%, spirituality with 50% and social and self-control skills with 54%. On the other hand, the risk factors found in the female sex are preconceptions and assessment of PAS with 38% and emotional discomfort with 32%, while in men the preconceptions and assessment of PAS were found with 30%, emotional discomfort, spirituality with 26% and social permissiveness and accessibility to SPA with 24%. In this sense, women have interpersonal relationships as protective factors with 42%; spirituality, social and self-control skills, social permissiveness and accessibility to SPA with 34%. In turn, in men, interpersonal relationships prevail as a protective factor with 28% and social skills with 20%. Conclusion: the design, elaboration, implementation and application of prevention programs in the family and school environment should be objectives to be taken into account by the organizations and institutions related to the problem of drug use in adolescents.